Chronic Loss of CA2 Transmission Leads to Hippocampal Hyperexcitability - Boehringer, Roman; Polygalov, Denis; Huang, Arthur J Y; Middleton, Steven J; Robert, Vincent; Wintzer, Marie E; Piskorowski, Rebecca A; Chevaleyre, Vivien; McHugh, Thomas J (Neuron (Cambridge, Mass.), 2017)
Hippocampal CA2 pyramidal cells project into both the neighboring CA1 and CA3 subfields, leaving them well positioned to influence network physiology and information processing for memory and space. While recent work has suggested unique roles for CA2, including encoding position during immobility and generating ripple oscillations, an interventional examination of the integrative functions of these connections has yet to be reported. Here we demonstrate that CA2 recruits feedforward inhibition in CA3 and that chronic genetically engineered shutdown of CA2-pyramidal-cell synaptic transmission consequently results in increased excitability of the recurrent CA3 network. In behaving mice, this led to spatially triggered episodes of network-wide hyperexcitability during exploration accompanied by the emergence of high-frequency discharges during rest. These findings reveal CA2 as a regulator of network processing in hippocampus and suggest that CA2-mediated inhibition in CA3 plays a key role in establishing the dynamic excitatory and inhibitory balance required for proper network function.